Analysis of the Dynamics of Islamic Educational Law and Policy to Improve Teacher Professionalism in Indonesia - Hilmin Hilmin; Masnila Masnila; Eva Sunarya; Dwi Noviani (ANWARUL, 2025)
This study examines the dynamics of Islamic education law and policy in Indonesia and their role in enhancing educator professionalism, employing a qualitative method through an extensive literature review. The analysis reveals that Islamic education law and policy in Indonesia are continually evolving to address emerging educational needs and the demands of a rapidly changing social, technological, and global landscape. These legal and policy developments prioritize the enhancement of human resource quality, particularly educators, and exert a significant influence on the national education system through regulatory frameworks that foster character development and academic competence. Professionalism in Islamic education encompasses the advancement of educators' knowledge, skills, and attitudes to effectively navigate the challenges of modern education. The legal framework plays a vital role in supporting this professionalism by establishing competency standards, implementing certification systems, and ensuring legal protection for educators. The study concludes that the synergy between evolving legal frameworks, Islamic education policies, and professional development initiatives is fundamental to improving the overall quality of education in Indonesia.